2020
DOI: 10.3390/ani10101813
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and Liposoluble Vitamins in the Plasma and Tissues of Light Lambs Given Different Maternal Feedings and Fattening Concentrates

Abstract: The carotenoids and liposoluble vitamins in the plasma and tissues of the lambs under different maternal feedings and fattening concentrates was studied. During lactation, 21 lambs were housed with their dams, that received a total mixed ration (intensive); 21 ewe–lamb pairs grazed on alfalfa; and 21 pairs grazed on sainfoin. After weaning, half of the lambs in each maternal feeding group received a commercial concentrate (control) and the other half a concentrate with quebracho (Schinopsis balansae), as a sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 48 publications
(96 reference statements)
2
8
0
3
Order By: Relevance
“…Both studies found that fat from grass-fed lambs contained more retinol than fat from compound-fed lambs. Rufino-Moya et al [ 23 ] obtained the same results as previous authors [ 20 , 22 ] regarding kidney and subcutaneous fat while observing no differences in intramuscular fat. The fat retinol values in our study were higher than those obtained by Blanco et al [ 22 ] in the kidneys and subcutaneous fat of suckling lambs and by Rufino-Moya et al [ 23 ] in intramuscular fat, kidneys, and subcutaneous fat of suckling lambs that were fattened with dietary concentrates after weaning.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…Both studies found that fat from grass-fed lambs contained more retinol than fat from compound-fed lambs. Rufino-Moya et al [ 23 ] obtained the same results as previous authors [ 20 , 22 ] regarding kidney and subcutaneous fat while observing no differences in intramuscular fat. The fat retinol values in our study were higher than those obtained by Blanco et al [ 22 ] in the kidneys and subcutaneous fat of suckling lambs and by Rufino-Moya et al [ 23 ] in intramuscular fat, kidneys, and subcutaneous fat of suckling lambs that were fattened with dietary concentrates after weaning.…”
Section: Resultssupporting
confidence: 79%
“…Rufino-Moya et al [ 23 ] obtained the same results as previous authors [ 20 , 22 ] regarding kidney and subcutaneous fat while observing no differences in intramuscular fat. The fat retinol values in our study were higher than those obtained by Blanco et al [ 22 ] in the kidneys and subcutaneous fat of suckling lambs and by Rufino-Moya et al [ 23 ] in intramuscular fat, kidneys, and subcutaneous fat of suckling lambs that were fattened with dietary concentrates after weaning. On the other hand, Osorio et al [ 60 ] stated that kids that were fed a milk replacer had higher retinol concentrations in the Longissimus dorsi muscle and in various muscles of the leg than kids that were fed natural milk.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The FA proportions of fresh sainfoin, hay and silage are in line with those reported by Lobón et al, 9 Toral et al 23 and Girard et al, 24 respectively. Previous work has reported data for the carotenoids and tocopherols in fresh sainfoin, 25,26 but not for silage or hay. Cabiddu et al 27 reported the FA profiles for fresh sulla at different stages and Priolo et al 28 reported that fresh sulla before flowering contained the most abundant C18:3 n-3, C16:0 and C18:2 n-6 contents, but no data on the FA, carotenoids, tocopherols and antioxidant activity of preserved sulla are available.…”
Section: Discussionmentioning
confidence: 92%